Interpreting and tailoring affordance based design user-centered experiments. Issue 1 (2nd January 2020) - Chen, Mo; Mata, Ivan; Fadel, Georges
ABSTRACT: The identification, selection, and consideration of appropriate affordances during the preliminary design phase of a product play a critical role in the process of Affordance Based Design (ABD). A design tool named Affordance Based Interactive Genetic Algorithm (ABIGA) evolves products by having designers identify, and then users assess the affordance qualities of virtual prototypes. Affordances are defined to be perceived interactions, both positive and negative, primarily between the user and the artifact. In order to achieve a successful product evolution, guidelines are proposed to help designers in the setting up of experiments related to user-centered design and ABD specifically. It was found that the existence of conflicting affordances would result in a slower evolution when compared with one that did not have such conflicts. Meanwhile, it was observed that virtual presentation does influence the users' judgments. From these observations, hypotheses and multiple experiments, these guidelines are discussed and critiqued to provide designers with insight into how to control user-centered experiments.